Effects of Thermal Radiation and Variable Porosity on Unsteady Magnetoconvective Heat-Mass Transport Past a Vertical Perforated Sheet - Md. Abu Bkar PK; Md. Hasanuzzaman; Md. Mosharof Hossain; Dipayan Mondal (Journal of Engineering)
This study interprets the effects of radiative and variable porosity on a time-dependent MHD-free convective heat-mass transfer past a vertical porous sheet. The PDEs governing the research are converted into nondimensional ODEs by inserting the similarity transformation containing a set of physical parameters. The numerical results are found by using the finite difference method through MATLAB with the help of the shooting technique. The roles of emerging nondimensional numbers/parameters, such as the Darcy number (Da), Prandtl number Pr, magnetic force parameter (M), thermal radiation parameter (R), chemical reaction parameter Kr, and suction parameter v0, on fluid flow have been observed within the boundary layer. The fluid motion enhances uplifting quantities of radiative parameter and Darcy number. The fluid temperature goes up for growing amounts of thermal radiation and Dufour number. The fluid mass decays to improve the Schmidt number and suction parameter. The local friction coefficient rises about by 32%, 12%, and 15% owing to improving values of Da from 0.5 to 2.0, R from 0.5 to 2.0, and Df from 0.5 to 3.5, respectively. The heat transfer falls down about by 33%, 35% due to enhancing values of R from 0.5 to 2.0, and Df from 0.5 to 3.5, respectively. At last, we looked at our numerical results in relation to previously published articles and discovered that there was a good agreement.